Skills' Substitutability and Technological Progress: U.S. States 1950-1990 - Antonio Ciccone; Giovanni Peri (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this article we estimate the long-run aggregate elasticity of substitution between skilled and unskilled workers. This is an important parameter as it allows us to compute the skill biased technological progress (SBTP) from the evolution of relative wages. However, it is hard to estimate because skill supply is endogenous. We tackle the task by using instruments proposed by the labor literature as sources of exogenous variation of schooling achievements across U.S. States. They are the state laws on Compulsory Schooling Attendance and on Child Labor. We then calculate SBTP and, using growth accounting, we calculate Hicks neutral technological progress (HNTP) for U.S. states in each decade between 1950 and 1990.
Keywords: 330; elasticity of substitution; skill biased technology; skilled and unskilled workers; U.S. states